KEPEMILIKAN INSTITUSIONAL DAN KONFLIK KEAGENAN DI PASAR MODAL INDONESIA - Prasetyo, Teguh (Jurnal MS, 2014)
This research aims to test the agency theory in Indonesian capital market was proxied by the variable mechanism controlling the agency conflicts, based on institutional ownership. The data used in this study is secondary data drawn from the Osiris database, ICMD. It is industrial company, excepted insurance companies and financial services that meet the criterian sampling and it was listed on the Indonesia Stock Exchange (BEI). The data is in the form of pooled data with the observation period from the year 2004-2010. Variables used in this study is that the company's performance to the performance of utility assets and Tobin's q accounting for market performance as a proxy for agency conflicts as well as the dependent variable. As for institutional ownership as independent variables and firm size as a control variable. The method of analysis used in this study is multiple regression of pooled data analysis. The results of this study is an institutional ownership has a positive effect on performance. That is, institutional ownership having character to control the agency conflict. With the result that, institutional ownership has been play function of binding and oversight of agency conflict.